Genetic heterogeneity of hepatocellular carcinoma. - Unsal, H (1994)
We studied 80 hepatocellular carcinomas from three continents for p53 gene (TP53) mutations and hepatitis B virus (HBV) sequences. p53 mutations were frequent in tumors from Mozambique but not in tumors from South Africa, China, and Germany. Independent of geographic origin, most tumors were positive for HBV sequences. X gene coding sequences of HBV were detected in 78% of tumors, whereas viral sequences in the surface antigen- and core antigen-encoding regions were present in less than 45% of tumors. These observations indicate that hepatocellular carcinomas are genetically heterogeneous. Mozambican-type of hepatocellular carcinomas are characterized by a high incidence of p53 mutations related to aflatoxins. In other tumors, the rarity of p53 mutations combined with the frequent presence of viral X gene coding sequences suggests a possible interference of HBV with the wild-type p53 function.